Actors in conflict and competition for living space in the Poboya gold mining area, Palu City, Central Sulawesi - Moh Nutfa; Zaiful Zaiful; Suriansah Suriansah; Restu Monika Nia Betaubun; Ratnah Rahman (Jurnal Sosiologi Dialektika, 2025)
The conflict in the Poboya mining area has not ended due to the large number of parties involved in the conflict and conflict resolution has not been achieved optimally when the parties involved continue to risk strength for the struggle for living space. Social conflict mapping is needed as a conflict resolution step. This research aims to identify conflict patterns and analyze conflict relations between actors in the Poboya gold mining area of Palu City. A descriptive qualitative approach was used to extract empirical data through observation methods, in-depth interviews, and news searches related to conflict phenomena. Data were analyzed interpretatively through an interactive analysis model including data reduction, data display and data verification. Meanwhile, data validity was carried out through the triangulation method. The results showed that conflict patterns stemmed from the continuous struggle for territory. Conflict has two characteristics, namely latent and manifest. The existence of conflict follows the existence and relations between actors in the conflict scheme. It is concluded that the mining industry creates social conflict vulnerabilities that are difficult to end. The findings of this research indicate the need for conflict management and resolution in mining areas.